2023
DOI: 10.7759/cureus.35771
|View full text |Cite
|
Sign up to set email alerts
|

Overall Clinical Features of Type 2 Diabetes Mellitus With Respect to Gender

Abstract: IntroductionSince patients with type 2 diabetes are frequently misdiagnosed, provided inappropriate management, or poorly controlled, it is important to comprehend the wide range of clinical signs and symptoms associated with diabetes. Therefore, this study evaluated the overall clinical manifestations of patients with type 2 diabetes patients with respect to gender. MethodsThis was a multicenter, cross-sectional study that was conducted at various hospitals, using a nonprobability sampling technique. The dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A Japanese study found a strong connection between the LAP and diabetes mellitus in both sexes [45]. The clinical features of diabetes differ between the sexes [46]. An American study reported that the whole blood Se concentration was higher in male non-smokers [47].…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study found a strong connection between the LAP and diabetes mellitus in both sexes [45]. The clinical features of diabetes differ between the sexes [46]. An American study reported that the whole blood Se concentration was higher in male non-smokers [47].…”
Section: Discussionmentioning
confidence: 99%
“…The MEME Suite, accessible at https://meme-suite.org/meme/tools/meme, was utilized to identify protein motifs encoded by these genes. Additionally, an online tool was employed to pinpoint the locations of these motifs within the peptide sequences (Haider et al, 2023b).…”
Section: Gene Characterization and Structure Analysis Of Npr1-like Genesmentioning
confidence: 99%
“…The Ka/Ks ratio was assessed to elucidate the molecular evolutionary rates of each gene pair. Generally, a Ka/Ks value <1 suggests purifying selection in evolution, Ka/Ks equals to 1 indicates neutral selection, while Ka/ Ks >1 signifies positive selection (Haider et al, 2023b). Furthermore, the calculation of the divergence time for these gene pairs was conducted using the formula t = Ks/2r, with r (1.5 × 10 −8 ) serving as the representative value for neutral substitution rates (Campos et al, 2023).…”
Section: Nonsynonymous (Ka) and Synonymous (Ks) Substitution Rates Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Women with major depressive disorders (MDD), for example, have been found to have a strong linkage with diabetes mellitus, which is a factor contributing to MDD 19 . In addition, diabetes mellitus is an important factor in stimulating several other health outcomes, such as muscle discomfort, urinary signs, neurological signs, and skin-related indications 20 . Comparing among ages, men have a higher likelihood of developing diabetes at a younger age, in particular individuals who have a lower body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%